The Improvement of RAPD-PCR Molecular Marker Efficiency in Detection of Polymorphism in Fennel (Foeniculum vulgar) Using Restriction Enzymes - A Etminan; L Shooshtari; M Ghorbanpour; A Mehrafarin; A Qaderi (Institue of Medicinal Plants, ACECR, 2013)
Background: Fennel (Foeniculum vulgar) is a medicinal plant species in the Apiaceae family with culinary and medicinal uses. Objective: This study was conducted to evaluate the effects of enzymatic digestion of PCR product in improvement of the efficiency of RAPD markers. Methods: Nine RAPD primers were used to amplify the genomic DNA of fifteen accessions of Fennel. Following amplification, a part of PCR products was digested with two restriction enzymes (EcoRI and MseI). Both of digested and undigested PCR products were separated on agarose gel electrophoresis. The accessions were grouped by cluster analysis and polymorphic information content index was calculated for each marker. Also percentage and component of essential oil were indicated by GC/MS analysis. Results: The comparison of banding patterns of digested and undigested PCR products revealed that digestion of RAPD-PCR product using a four base cutter enzyme such as Mse I shows a higher level of polymorphism as compared to standard RAPD. Cluster analysis based on data obtained by modified RAPD classified accessions more suitable as compared to standard RAPD data. There was no correlation between genetic diversity and metabolic yield. Conclusion: Restriction enzymes have enormous potential to improve the efficiency of RAPD markers in evaluation of genetic diversity across genome.